The Impact of COVID-19 Pandemic, Financial Wellness, and Online Teaching on Schoolteachers’ Mental Health: A Cross-Sectional Study in Lebanon - Baroud, Tarek; El Masri, Jad; Shammaa, Hadi; Saleh, Mustafa; Chanbour, Hani; Salemeh, Pascale (International Journal of Clinical Research, 2022)
Background: Teaching is a mentally and physically draining occupation, and due to the SARS-CoV-2 pandemic, the education system shifted to online platforms, which made it even harder. Lebanon is a developing country that is not well prepared for such a daunting outbreak. In addition to its tremendous economic crisis, it will be even harder for teachers to maintain mental stability. The aftermaths of this crisis could, perhaps, impact all the fundamental systems within the country including education Aim: This study aims to assess stress, anxiety, and depression levels among Lebanese schoolteachers based on the COVID-19 outbreak, the Lebanese economic crisis, and online education. Methods: A cross-sectional study was carried out, enrolling 300 schoolteachers currently working in Lebanon. An online survey was used, assessing sociodemographic factors, teaching status, financial wellness, fear of COVID-19, and mental health. The IFDFW scale is used to assess financial distress, DASS-21 to assess psychological distress, and the COVID-19 fear scale to measure fear. Results: Results showed that 23% of teachers had severe depression, 25% had severe anxiety, and 16% had severe stress. Depression was correlated to both fear of COVID-19 and financial wellness (p<0.0001 for both). Anxiety and stress were correlated with online teaching (p<0.05), fear of COVID-19 (p<0.001), and financial wellness (p<0.001). Conclusion: Lebanese teachers showed severe levels of anxiety and stress as a consequence of online teaching, associated as well with depression when correlated with fear of COVID-19 and financial wellness. It is urgent to take measures to keep the Lebanese educational system productive, and dynamic, and prevent the storm of the stressful environment from worsening. Keywords: Anxiety, Depression, Stress, Online teaching, Pandemic, Economic crisis